Green jobs in the renewable energy sector - Bartniczak, Bartosz; Ptak, Michal (Leibniz, 2015)
"Green jobs exist for a long time. However, for some time dynamics of their creation is increasing and they are created in more and more sectors. Green jobs are created as a result of the development of new environmentally friendly technologies or through the "greening" of the next sectors of the economy. Despite the widespread use of the concept of green jobs there is a lack of a universally accepted definition of this concept and consequently can not be strictly defined sectors where these jobs are created. The purpose of this article is to present the situation related to the creation of green jobs in one of the fastest growing sectors in the world which is the renewable energy sector. The article analyzes the situation in selected countries, as well as in selected areas of renewable energy. The article presents also the support mechanisms that affect the development of the sector and thus to create jobs."